EFEK ANTIMIKROBA EKSTRAK Arcangelisia flava, Curcuma longa, Curcuma zanthorrhiza TERHADAP Bacillus DAN Pseudomonas PENYEBAB DIARE - Hujjastusnani, Noor; Amin, Astuti muh.; Nirmalasari, Ridha; Awaluddin, Annisa Maharani; Latifah, Nadia Dwi Nur; Riana, Rifa; Nisa, Khairun`; Ningsih, Ira Wahyu; Anisa, Nor (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Diarrhea is a major health issue often caused by Bacillus sp. and Pseudomonas aeruginosa. This study aims to evaluate the antibacterial activity of a combination of Arcangelisia flava, Curcuma longa, and Curcuma zanthorrhiza extracts against these bacteria. The research was conducted in vitro using a Completely Randomized Design (CRD) with extract concentrations of 30%, 50%, 75%, and 100%, along with positive and negative controls. Antibacterial tests were carried out using the disk diffusion method to measure the inhibition zones after 24, 48, and 72 hours of incubation. The results showed the highest inhibition zones at 100% concentration, reaching 1.38 mm for Bacillus sp. and 1.33 mm for Pseudomonas aeruginosa after 72 hours. This antibacterial activity is supported by active compounds such as flavonoids, alkaloids, and curcumin. In conclusion the combination of these extracts effectively inhibits diarrhea-causing bacteria and has potential as a safe herbal alternative to address antibiotic resistance.